Clinico-epidemiological profile and outcome of pleural effusion of infective etiology in children from central India - Rhishita Jha,; Bharani, Anjali; Dharmanshu Chaube, (Asian Journal of Medical Sciences, 2022)
Background: Empyema thoracis is an accumulation of pus in the pleural space. It is estimated that 0.6% of childhood pneumonias progress to empyema, affecting 3.3/1,00,000 children. Various treatment options available include antibiotics alone or with chest tube drainage, intrapleural fibrinolytics, video-assisted thoracoscopic surgery, and open decortications. Aims and Objectives: (1) The objective of the study was to study clinico-epidemiological and lab profile of pediatric patients with pleural effusion of infective etiology and (2) to study outcome and short term follow-up. Materials and Methods: Prospective observational study conducted from June 2020 to May 2021 at the pediatric department of a tertiary care hospital, central India. Inclusion criteria: Children between 6 months and 14 years diagnosed with pleural effusion clinically and radiologically. Exclusion criteria: Effusion of traumatic or malignant origin. Detailed history, examination, and relevant investigations were recorded. Data were compiled and analyzed. Patients were treated with intercostal drainage, antibiotics and were referred for surgical intervention wherever necessary. Results: Thirty-five patients were included in this study. The mean age of the patients was 4.4 years. Fever (100%), cough (88.5%) and breathlessness (65.7%) were the most common symptoms found at admission. Staphylococcus aureus was the most common organism isolated from pleural fluid. In the present study, 77% (27) patients were treated with ICD and antibiotics, 11.5% patients required surgical intervention, and 11.5% patients responded to antibiotics alone. The mortality rate in our study was 5.7% and the rest of the patients were successfully discharged and followed up. Conclusion: Antibiotics and tube thoracostomy are effective methods of treating pyogenic empyema thoracis in children in resource poor settings.